DEVELOPMENT OF INTERNAL MOTIVATION OF EDUCATIONAL ACTIVITY IN STUDENTS-ATHLETES ON THE BASIS OF USE OF HEURISTIC METHODS IN TEACHING SUBJECT "ANATOMY" - Vilchynskaya, Liudmila (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
In the article the role of heuristic methods of training in development of an intrinsic motivation of the educational activity of students of specialty "Physical culture" reveals. The methodological basis of research is constituted by pedagogical heuristics – methodology of training through own search. Content of heuristic training includes two parts: invariant which is set from the outside and is acquired by the student, and variable, created by each of them in the course of educational activity. The problem of research is formulated as a question: how it is possible to strengthen an intrinsic motivation of educational activities of students during teaching subject "Anatomy". The orientation of motivation of studying by students of subject "Anatomy" came to light by T. D. Dubovitskaya's test (reliability 0,935 (on Spirmen-Brown's formula) and 0,927 (on Cronbach's formula)). The data on change of dynamics of the academic progress of students confirming efficiency of heuristic methods are also provided in article.